Adiposopathy In Vitro Study The Effect of Toxoplasma Gondii Profilin Induction To The Expression of IL-6 and TNF-a as A Predictor Candidate of Adipocyte Dysfunction on Subcutan Adipocyte Culture - Sudjari Sudjari; Hendra Susanto; Rasjad Indra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
Metabolic syndrome is a group of several risk factors consist of hypertension, dyslipidemia, glucose intolerance disorder, obesity, and has a relationship with CVD pathomechanism. WHO was report in 2003 more than 300 million adult in the world suffered from obesity. The role of adipose tissue in infectious diseases and adipocyte quality changes after exposure to pathogen has not been revealed. On the other hand, the prevalence of infectious diseases in developing country is still high. Previous studies proved a relationship between infection of Toxoplasma gondii and tissue dysfunction. Profilin is a membrane component of Toxoplasma gondii that able to stimulate expression of proinflammation cytokines through TLR-11 upregulation, and predicted able to trigger the adipocyte dysfunction. The aim of this study are to knows the effect of profilin exposure in vitro on subcutaneous adipocyte to the expression of IL-6 and TNF-α. The measurement of IL-6 and TNF-a levels was done by ELISA technique. The result showed profilin exposure doses 5, 15 and 25 ng / ml increasing IL-6. Profilin exposure cause adipocyte dysfunction through the increasing proinflammatory adipocytokine levels as pathomechanism of metabolic syndrome associated with adipose tissue.